Monitoring Kinerja Heat Exchanger pada Sistem Sea Water & Cooling Water - Marwan Marwan; Mad Yusup; Ida Rosanti (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
One type of efficient and widely used heat exchanger is the Plate and Frame Heat Exchanger (PFHE). PFHE is a device designed to increase the efficiency of heat exchange through a structure of plates assembled together. This design allows a large heat exchange surface area in a relatively small space, creating an efficient environment for heat transfer. This study took the Plate and Frame type Heat Exchanger object, while the purpose of this study was to determine the performance of the Heat Exchanger in the Sea water & Cooling Water system at PT. Eni. The research methods used were the Observation method, Interview method (Question and Answer), and Literature review. The results of the study showed that the performance of the Heat Exchanger in the Sea water & Cooling Water system at PT. Eni runs according to the desired design. The operating temperature line remains below the maximum limit set, and indicates the performance of the heat exchanger in very good condition. This reflects the optimal heat exchange results in Cooling Water. In accordance with the design operating parameters, the achievement of heat exchange in the minimum range of 4 - 5 ℃ and the maximum limit of redistribution temperature in Cooling Water does not exceed 45 ℃, which indicates that this system operates according to the desired standards